Parent–infant closeness after preterm birth and depressive symptoms: A longitudinal study - Lehtonen, Liisa; Lilliesköld, Siri; De Coen, Kris; Toome, Liis; Gimeno, Ana; Caballero, Sylvia; Tameliene, Rasa; Laroche, Sabine; Retpap, Jana; Grundt, Hege; Van Hoestenberghe, Marie-Rose; Skene, Caryl; et al. (Frontiers in Psychology, 2022)
Background Preterm birth increases the risk for postpartum depression in both mothers and fathers, calling for strategies to alleviate and prevent depressive symptoms in parents of preterm infants. The aim of this study was to assess the association between early parent-infant closeness and later depressive symptoms among parents of preterm infants. We hypothesized that longer duration of closeness associate with fewer depressive symptoms in both parents. Methods This prospective cohort study included 23 neonatal intensive care units (NICUs) from 15 countries in 2018 to 2020. Each unit recruited families with preterm infants aiming to 30 families. The total duration of parents’ presence in the NICU, and separately parent-infant skin-to-skin contact and holding, were measured using a Closeness Diary up to 14 days. The Edinburgh Postnatal Depression Scale (EPDS) was used at discharge and at 4 months corrected age of the infant. Results The study included 684 mothers and 574 fathers. The median presence was 469 min (Q1 258 and Q3 1,087) per 24 h for the mothers and 259 min (Q1 100 and Q3 540) for the fathers; mean EPDS scores were 9.2 (SD 5.0) and 6.3 (SD 4.4) at discharge and 6.6 (4.7) and 4.3 (4.2) at 4 months, respectively. Parents’ presence and depressive symptoms varied greatly between the units. Parents’ presence as the total measure, or skin-to-skin contact and holding separately, did not associate with depressive symptoms in either mothers or fathers at either time point (adjusted). Conclusion No association was found between the duration of parent-infant closeness in the neonatal unit and parents’ depressive symptoms. The beneficial effects of family-centered care on parents’ depression seem to be mediated by other elements than parent-infant physical closeness. More research is needed to identify the critical elements which are needed to alleviate parents’ depression after NICU stay.